Novel method for measuring high-frequency wheel-rail force considering wheelset vibrations - Fubing Zhang; Hao Wang; Qihang Zeng; Pingbo Wu; Meiling Pan (Scientific Reports)
Abstract This article introduces a groundbreaking approach for accurately gauging high-frequency wheel-rail forces, taking into account the impact of wheelset vibration modes on measurement outcomes. The method relies on lateral and vertical acceleration data from the left and right axle box positions, combined with a finite element model, to determine the system’s frequency response function. Subsequently, it inverts the lateral and vertical wheel rail forces of both wheels. In terms of data processing, we employed the Fourier transform method, abandoning the traditional conversion to power spectral density functions. This improvement ensures that the phase information of the data is preserved, significantly enhancing the reliability of the results. To validate the reliability and accuracy of this method, a comparative study was conducted by establishing a model. Specifically, we conducted in-depth discussions on high-frequency wheel rail forces around 580 Hz. The comparison outcomes indicate a close correlation between the results obtained from SIMPACK’s direct simulation (5.7kN) and the inverse method (5.2kN). These findings robustly support the theoretical accuracy and practical feasibility of this method.